A Sugar Transporter Takes Up both Hexose and Sucrose for Sorbitol-Modulated In Vitro Pollen Tube Growth in Apple. Issue 2 (11th December 2019) - Li, Chunlong; Meng, Dong; Piñeros, Miguel A.; Mao, Yuxin; Dandekar, Abhaya M.; Cheng, Lailiang
Abstract : A sugar transporter protein, STP13a, mediates the uptake of both hexose and Suc for in vitro pollen tube growth in apple, with its expression regulated by sorbitol via a MYB transcription factor. Abstract: Rapid pollen tube growth requires uptake of Suc or its hydrolytic products, hexoses, from the apoplast of surrounding tissues in the style. Due to species-specific sugar requirements, reliance of pollen germination and tube growth on cell wall invertase and Suc or hexose transporters varies between species, but it is not known if plants have a sugar transporter that mediates the uptake of both hexose and Suc for pollen tube growth. Here, we show that a sugar transporter protein in apple ( Malus domestica ), MdSTP13a, takes up both hexose and Suc when expressed in yeast, and is essential for pollen tube growth on Glc and Suc but not on maltose. MdSTP13a-mediated direct uptake of Suc is primarily responsible for apple pollen tube growth on Suc medium. Sorbitol, a major photosynthate and transport carbohydrate in apple, modulates pollen tube growth via the MYB transcription factor MdMYB39L, which binds to the promoter of MdSTP13a to activate its expression. Antisense repression of MdSTP13a blocks sorbitol-modulated pollen tube growth. These findings demonstrate that MdSTP13a takes up both hexose and Suc for sorbitol-modulated pollen tube growth in apple, revealing a situation where acquisition of sugars for pollen tube growth is regulated by a sugar alcohol.